Preparation of AlN micro-honeycombs with high permeability via freeze-casting. Issue 13 (October 2020) - Wei, Zhilei; Xie, Wenqi; Zhang, Xiaoyu; Zhang, Zhejian; Li, Yanjun; Xia, Hongyan; Wang, Bo; Shi, Zhongqi
Highlights: Highly permeable AlN micro-honeycombs (AlN-Hs) were successfully fabricated via freeze-casting. The microstructure, open porosity, and N2 gas permeability of the AlN-Hs can be controlled by adjusting the solid loadings. The as-fabricated AlN-H with an open porosity of 64.9% display high N2 gas permeability and essential compressive strength. The AlN-Hs have shown significant promise for application in catalyst supports or filters. Abstract: Highly permeable AlN micro-honeycomb (AlN-H) ceramics with unidirectional macropore channels and porous struts were fabricated via tertiary butyl alcohol (TBA)-based freeze-casting. The effect of the AlN solid loading of the freezing slurries on the microstructure, open porosity, N2 gas permeability, and compressive strength of the as-prepared AlN-Hs were systematically investigated. The results showed that the honeycomb structure and open porosity of the AlN-Hs can be adjusted by altering solid loading. With the increase in solid loading from 10 vol% to 30 vol%, the approximate pore channel size of the AlN-Hs decreased from 50.1 μm to 15.6 μm, strut thickness increased from 8.2 μm to 16.6 μm approximately, and the corresponding open porosity decreased from 87.6–56.6%. The as-fabricated AlN-H with an open porosity of 64.9% possessed high N2 gas permeability and essential compressive strength and can be used as a catalyst support or filter in industries.